Clinical control study of traditional Chinese medicine hot compress combined with traction in the treatment of cervical spondylotic radiculopathy: Study protocol. Issue 4 (29th January 2021) - Ding, Xing; Wu, Jinze; Shen, Qixing; Xu, Jinhai; Mo, Wen
Abstract : Abstract: Cervical spondylotic radiculopathy (CSR) is the most common type of cervical spondylosis, accounting for about 60% of the incidence of cervical spondylosis. Both cervical traction and traditional Chinese medicine hot compress are common and effective treatment for CSR. This study will be performed to investigate the effect of a combination of cervical traction and traditional Chinese medicine hot compress on CSR. In this non-blinded, randomized controlled trial, 100 eligible patients will be randomly divided into a treatment group (intermittent cervical traction combines with traditional Chinese medicine hot compress) and a control group (intermittent cervical traction combined with hot compresses). Before and after the intervention, the Visual Analog Scale score, Neck Disability Index score, and 20-score scale of symptoms will be evaluated at baseline and at 7, 14, 21, and 28 days. During the treatment period, any signs of acute adverse events, such as paralysis of aggravated pain, nausea, dizzy, and even syncope, will be recorded at each visit. Although intermittent cervical traction and traditional Chinese medicine hot compress have been used in the treatment of CSR in China for many years, there is no consensus on its effectiveness of combination therapy. This experiment will provide convincing evidence of the efficacy of intermittent cervical traction combined with traditional Chinese medicine hot compress in the treatment of CSR.